NEMATODES FROM MAMMALS IN BRAZIL: AN UPDATING - Magalhães Pinto, Roberto (2011)
The present findings update of previously published results on the nematodes parasitizing Brazilian mammals, with the inclusion of other genera, species and hosts. Measurements and illustrations are only related to the nematodes representing new taxa, and to those that were either redescribed or reported in Brazil occurring in mammals since 1997: Ancylostoma pluridentatum (Alessandrini, 1905), Angiostrongylus lenzii Souza, Simões, Thiengo, Lima, Mota, Rodrigues-Silva, Lanfredi, Maldonado Jr, 2009, Anisakis physeteris Baylis, 1923, A. simplex (Rudolphi, 1808) Dujardin, 1845, A. typica (Diesing, 1860), Anisakis sp., Ascaris elongata (Rudolphi, 1819), Avellaria intermedia Durette- Desset, Gonçalves & Pinto, 2006, Cheiropteronema globocephala Sandground, 1929, Contracaecum sp., Dentostomella translucida Schulz & Krepkorgorskaya, 1932, Freitastrongylus angelae Gonçalves, Pinto & Durett-Desset, 2007, Gracilioxyuris agilisis Feijó, Torres, Maldonado Jr & Lanfr edi, 2008, Guerrerostrongylus zetta (Tavassos, 1937) Sutton & Durette-Desset, 1991,Hadrostrongylus speciosum Hoppe & Nascimento, 2007, Halocercus (Posthalocercus) kleinenbergi Delyamure, 1951, Litomosoides chagasfilhoi Moraes Neto, Lanfredi& Souza, 1997, Litomosoidesodilae Notarnicola & Navone, 2002, Longistriata myopotami Petrov & Sadykov, 1969, Moennigia littlei Durette-Desset, 1970, Molinema nattereri Guerrero & Bain, 2001, Parabronema pecariae Ivaschkin, 1960, Physaloptera herthameyrae Torres, Maldonado Jr & Lanfredi, 2009, Pseudoterranova sp., Pterygodermatites (Multipectines) pluripectinata Hoppe, Lima, Tebaldi, Nascimento, 2010, Stenurus globicephalae Baylis & Daubney, 1925, Stilestrongylus lanfrediae Souza, Digiani, Simões, Luque, Rodrigues-Silva & Maldonado Jr, 2009, Syphacia carlitosi Robles & Navone, 2007, Syphacia kinsellai Robles & Navone, 2007, Syphacia mesocriceti Quentin, 1971, Thelazia californiensis Price, 1930, Trichofreitasi alenti Sutton &Durette-Desset, 1991, Trichuris didelphis Babero, 1960, Trichuris opaca Barker & Noyes, 1915, Trichuris thrichomysi Torres, Nascimento, Menezes, Garcia, Santos, Maldonado Jr, Miranda, Lanfredi & Souza, 2011, Viannella trichospicula Durette-Desset Gonçalves & Pinto, 2006. In addition, checklists of other mammalian hosts for nematode species that already had been referenced in the previous catalogue, are included in the present survey.